Avast report highlights IoT vulnerabilities. Issue 1 (January 2019) - Unknown
Abstract : The latest 'Threat Landscape Report' from Avast highlights the problem of vulnerable Internet of Things (IoT) devices which form a key element in an ever-growing attack surface.